'Sie lieber Hans Brandenburg'. Gertrud Leistikow and Hans Brandenburg. (May 2016) - Boer, Jacobien de
Abstract : Hans Brandenburg (1885–1968) was one of the first authors of his time to write seriously about modern dance. His book Der moderne Tanz (Modern dance) can be seen as an important source for dance historians. The best known contemporary dancers are discussed as are the schools that Brandenburg considered of relevance for this new art. Brandenburg seems to have been especially impressed by the dancer Gertrud Leistikow (1885–1948) with whom he and his wife Dora Brandenburg-Polster corresponded regularly from 1912 onwards. 1 He regarded her as a great artist, a genius even. It is remarkable that the career of Gertrud Leistikow has remained relatively underexposed, which may also be the reason for various misconceptions about her. 2 One of these is that she was a Nackttänzerin (nude dancer), ashamed of her face and wearing masks or veils to hide it. 3 Using Brandenburg's works and his correspondence with Leistikow (of which only the letters written by Leistikow survive) this essay evaluates Leistikow's role in the emergence of modern dance, deals with misunderstandings and also provides some explanations for her disappearance in obscurity.